2013
DOI: 10.1007/978-3-642-37057-1_4
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Synthesis Process for Choreography Realizability Enforcement

Abstract: Abstract. The near future in service-oriented system development envisions a ubiquitous world of available services that collaborate to fit users' needs. Modern service-oriented applications are often built by reusing and assembling distributed services. This can be done by considering a global specification of the interactions between the participant services, namely the choreography. In this paper, we propose a synthesis approach to automatically synthesize a choreography out of a specification of it and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…The work described in this paper represents an advance also with respect to our previous work in [11,12]. In fact, although the synthesis process described there treats most of the BPMN2 constructs, it considers a simplified version of their actual semantics.…”
Section: State Of the Art And Beyondmentioning
confidence: 94%
See 1 more Smart Citation
“…The work described in this paper represents an advance also with respect to our previous work in [11,12]. In fact, although the synthesis process described there treats most of the BPMN2 constructs, it considers a simplified version of their actual semantics.…”
Section: State Of the Art And Beyondmentioning
confidence: 94%
“…Essentially, the developed ATL transformations consist of a number of rules each devoted to the management of specific BPMN2 modeling constructs. The current implementation of these transformations within CHOReOSynt (available at choreos.disim.univaq.it) extends and advances their preliminary version in [11,12].…”
Section: Figure 2 Process Overviewmentioning
confidence: 96%
“…Further research problems have been identified and investigated for distributed choreographies, for instance realizability [22,23,18,24], conformance [25,26,27,28], or enforcement [29]. Our work departs from the existing literature in that we does not require to start from a global description of the interactions.…”
Section: On Choreography and Orchestration: Related Workmentioning
confidence: 99%
“…Note that, although for each choreography participant a suitable third-party service may have been discovered (and hence, its interaction protocol fits the behavior of the participant in isolation), the uncontrolled (or wrongly coordinated) composite behavior of all the discovered services may show undesired interactions that prevent the choreography realization. For a detailed and formal description of the notion of undesired interaction, refer to [4,6,9].…”
Section: Choreosynt: Automated Synthesis Of Service Choreographiesmentioning
confidence: 99%
“…The research we described in this paper is an advance over our previous research [4,6]. Although the synthesis process described in our previous research treated most BPMN2 constructs, it considered a simplified version of their actual semantics.…”
Section: Related Workmentioning
confidence: 99%